Pyrolysis of polypropylene plastic waste into carbonaceous char: priority of plastic waste management amidst COVID-19 pandemic - Harussani, M.m.; Sapuan, S.m.; Rashid, Umer; Khalina, A.; Ilyas, R.A. (Elsevier, 2021)
COVID-19 global pandemic, originated from Wuhan, resulted in a massive increase in the output of polypropylene (PP)-based personal protective equipment (PPE) for healthcare workers. The continuous demand of PPE across the world caused the PP based plastic wastes accumulation. Some alternative approaches that have been practiced apart from collecting the plastic waste in the landfills are incineration approach and open burning. However, there were many drawbacks of these practices, which promote the release of chemical additives and greenhouse gases into the environment. Therefore, a proper approach in treating the plastic wastes, which introduces conversion of plastic wastes into renewable energy is paramount. Along the way of extensive research and studies, the recovery of PP plastic to fuel-like liquid oil and solid char through thermal decomposition of pyrolysis process, helps in reducing the number of PP plastic wastes and produces good quality pyrolysis liquid oil and solid char to be used in fuel applications. This paper summarizes the pyrolysis process for massively produced PP plastic wastes, type of pyrolysis used and the main pyrolysis parameters affecting the product yields. Literature studies of pyrolysis of PP plastic and several key points to optimize solid char production for PP were thoroughly elaborated in this review paper.